2020
DOI: 10.1002/cyto.a.24291
|View full text |Cite
|
Sign up to set email alerts
|

Practical application of microsphere samples for benchmarking a quantitative phase imaging system

Abstract: Quantitative phase imaging (QPI) provides an approach for monitoring the dry mass of individual cells by measuring the optical pathlength of visible light as it passes through cells. A distinct advantage of QPI is that the measurements result in optical path length quantities that are, in principle, instrument independent. Reference materials that induce a well‐defined optical pathlength shift and are compatible with QPI imaging systems will be valuable in assuring the accuracy of such measurements on differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Optical volume and refractive index measurements of polystyrene beads with this system agree with what we expect from known material properties ( Fig. 11 ) as well as previous characterization of commercial systems [26] , [27] , [28] , [29] . In previous work we have shown that measurements of cell mass and growth performed with a system based on these plans agree with commercial systems as well as independent measurements of cell growth [11] .…”
Section: Discussionsupporting
confidence: 88%
“…Optical volume and refractive index measurements of polystyrene beads with this system agree with what we expect from known material properties ( Fig. 11 ) as well as previous characterization of commercial systems [26] , [27] , [28] , [29] . In previous work we have shown that measurements of cell mass and growth performed with a system based on these plans agree with commercial systems as well as independent measurements of cell growth [11] .…”
Section: Discussionsupporting
confidence: 88%
“…A typical origin of these disturbances are internal reflections which can be caused by the entire optical imaging path and depend on the individual system alignment. This underlines the importance of QPI system benchmarking as recently addressed in a study of National Institute of Standards and Technology (NIST) [71] and the demand for specifically tailored test charts for QPI system performance quantification, for example as proposed in [46], with respect to interlaboratory assay variability studies.…”
Section: Discussionmentioning
confidence: 88%
“…A key factor influencing performance of 2D QPI methods is the focal position or location of the image plane along the optical axis, used for capturing phase images. QPI images taken out of focus show up to a 40% difference in measured optical volume differences for uniform microspheres, and QPI images of cells can show up to a 25% decrease in measured biomass compared to in focus QPI images . For 2D QPI, more planar adherent cells show greater measurement robustness with imperfect focal position relative to rounded cells, although there can be a significant difference in QPI dry mass data due to focus position even for flatter, adherent cells .…”
Section: Solving the Fundamental Problem Of Quantitative Phasementioning
confidence: 98%
“…However, there is variability in the refractive index of polystyrene, and typically large refractive index differences between polystyrene beads relative to cell culture media, combined with sharp “imaging edges” of these round beads, can lead to phase unwrapping artifacts that are not usually encountered with live cell samples. Potential phase unwrapping artifacts using polystyrene bead calibration standards can be mitigated by, for example, mounting the beads within material with a closer refractive index. , However, this approach also moves the calibration data range further from actual cell imaging conditions, which could impact experimental accuracy. Red blood cells have also been used as a phase calibration standard in the development of QPI methods because of their availability and fairly uniform shape and size. , Typically, nondiseased RBCs show a population dry mass variation of ∼15% .…”
Section: Solving the Fundamental Problem Of Quantitative Phasementioning
confidence: 99%